The revolution starts at home: Confronting intimate violence within activist communities - Chen, Ching-In; Dulani, Jai; Piepzna-Samarasinha, Leah Lakshmi (AK Press, 2016)
The Revolution Starts at Home is as urgently needed today as when it was first published. This watershed collection breaks the dangerous silence surrounding the “secret” of intimate violence within social justice circles. Just as importantly, it provides practical strategies for dealing with abuse and creating safety without relying on the coercive power of the state. It offers life-saving alternatives for survivors, while building a movement where no one is left behind.
Keywords: LGBTQIA2+; approches et analyses; identités LGBTQIA2+; justice sociale; militance; thématiques; violences; violences conjugales; violences contre les femmes*; violences d'état